Lawrence Grassi : from Piedmont to the Rocky Mountains - Costa, Elio, 1939-; Scardellato, Gabriele Pietro, 1951- (University of Toronto Press, 2015)
The definitive biography of this Canadian mountain hero, Lawrence Grassi will be essential reading for those interested in the history of immigration, sport, and the Rocky Mountains.